Answer: x=-2 y=2
Step-by-step explanation:
I decided that isolating the y value of the second equation is the best way to start solving.
I divide 3 from both sides to get y= (4-x)/3. With this, I can substitute into the first equation. 4x+3(4-x)/3)=-2.
The multiplying the 3 by the denominator three cancels each other out to make:
4x+4-x=-2.
We subtract 4 on both sides and then subtract x from 4x.
We end up with 3x=-6. Then, we divide both sides by 3.
x=-2.
Now we substitute this into the second equation to solve.
3y=4-(-2)
This becomes 3y=4+2 which is 3y=6
We divide both sides by 3 to get y=2
We end up with x=-2 and y=2.
I hope you learned something :)
Answer:
Maureen ignored the negative(minus) sign in 1.7 thereby turning it into positive 1.7
Step-by-step explanation:
-1.7 + (-6.3)
Correct simplification
-1.7 + (-6.3)
Open parenthesis
= - 1.7 - 6.3
= -8
NOTE:
- * + = -
- * - = +
+ * - = -
+ * + = +
Maureen's simplification
-1.7 + (-6.3)
= 1.7 - 6.3
= -4.6
Maureen ignored the negative(minus) sign in 1.7 thereby turning it into positive 1.7
The descent after 16 seconds would be 672 feet, with the function -42•X and X=16 so -42•16=-672
Answer:
Its 0.4 meters!
Step-by-step explanation: